2000
DOI: 10.1007/s002109900173
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deprivation, estrogen treatment and vascular function in male rat aorta

Abstract: The beneficial effects of estrogen on arterial function in women are well established, whereas studies concerning the vascular role of androgens have produced conflicting results. In the present study, we examined the effects of androgen deprivation and of estrogen treatment on vascular responses in male rats. Vascular reactivity was studied in aortic rings excised from intact and castrated rats, which had been implanted with capsules containing either 17beta-estradiol (E2) or its vehicle for 5 days. Contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…We have recently reported that neither estrogen treatment nor androgen deprivation elicited beneficial effects in terms of vascular reactivity in the aorta from non-diabetic male rats (Cignarella et al 2000). In view of the antithetical results from the present study, one can clearly understand that diabetes is a critical determinant for the vascular effects of sex hormones in both female and male rats.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We have recently reported that neither estrogen treatment nor androgen deprivation elicited beneficial effects in terms of vascular reactivity in the aorta from non-diabetic male rats (Cignarella et al 2000). In view of the antithetical results from the present study, one can clearly understand that diabetes is a critical determinant for the vascular effects of sex hormones in both female and male rats.…”
Section: Discussionmentioning
confidence: 64%
“…We recently reported on the effects of sex steroids on vascular function in male non-diabetic rats (Cignarella et al 2000). In the present study, we sought to determine the effects of estrogen treatment on vascular function in male diabetic rats by evaluating aortic responses to a number of vasoactive mediators as well as the generation of vasoactive eicosanoids in both intact and gonadectomized animals.…”
Section: Introductionmentioning
confidence: 99%
“…anesthesia. Four weeks later, the castrated animals received a subcutaneous implant of two silastic capsules containing 25 l of vehicle (peanut oil) or E 2 (5.87 g; 0.86 mM) for 5 days (Bolego et al, 1999;Cignarella et al, 2000). Plasma E 2 concentrations after this treatment approached the normal rat proestrus level (Lapchak, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Orchiectomy in male rats has also been demonstrated to have no effect on KCl-induced stress and Ca 2+ influx [39] or phorbol 12,13-dibutyrate-induced contraction [12] . However, it has been reported that contraction to norepinephrine was enhanced in aortae from male rats castrated for 4 weeks [40] . The discrepancies between the different studies may be due to the different hormone deprivation regimen as well as the contracting agent.…”
Section: Discussionmentioning
confidence: 99%